AKTUALISASI NILAI INSAN KAMIL DALAM PENDIDIKAN MADRASAH UNTUK MENGHADAPI DEGRADASI MORAL GENERASI DIGITAL - Muhammad Alif Dwiki Ramadhan; Annisa Nurul Zannah; Saripudin; Rifqi Khairul Anam (Darussalam, 2026)
The rapid expansion of digital technology has significantly altered student behavior in madrasah education, manifesting in declining communication ethics, weakened respect for authority, and increasing individualism. Despite these challenges, madrasah education often remains fixated on cognitive and academic achievements, leaving a void in character and spiritual development. This study aims to analyze the relevance of the Insan Kamil concept as a fundamental paradigm of Islamic Educational Philosophy in responding to the moral degradation of the digital generation. Using a qualitative library research method (2022-2025), the study explores how this concept serves as a framework for an Ontological Restoration that shifts the focus from mere information processing to the restoration of human nature (fitrah). The findings reveal that Insan Kamil offers a holistic balance between intellectual, spiritual, and social responsibility. By implementing this framework, madrasahs can move beyond technical digital literacy toward a deeper existential awareness where technology is mastered as a tool for transcendental purposes. The study concludes that an ontological approach to the Insan Kamil values, encompassing teacher role modeling, moral habituation, and spiritual self-control, is essential to forming ethically grounded students capable of navigating modern disruptions without losing their moral identity.